Factors Influencing Parents’ Decision-Making in Sending Their Children to Public Primary Schools in Luang Prabang Municipality, Luang Prabang Province - YIAMACANG, suechang; PHIMMAVONG, Kongsy; VONGSIPASEAUTH, Bounmor; ONSENGTAVANH, Fongmany; KHAMMELEESAYSUE, Her (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This is a quantitative research study that aims to: 1) study of parents’ decision-making in sending their children to public primary schools in Luang Prabang Municipality, Luang Prabang Province; 2) study of parents’ opinions on factors influencing their decision to send their children to public primary schools in Luang Prabang Municipality, Luang Prabang Province; and 3) study factors influencing parents’ decision making in sending their children to public primary schools in Luang Prabang Municipality, Luang Prabang Province. The population of this study consisted of parents of students enrolled in 20 public primary schools in the Luang Prabang Municipality, Luang Prabang Province, in the 2025–2026 academic year. The sample size of 346 participants was determined using the Krejcie and Morgan table. The research instrument was a 5-point scale questionnaire. The data were analyzed using descriptive statistics to determine the mean () and standard deviation (S.D), as well as inferential statistics, specifically Multiple Regression Analysis. The results of this study indicated that: 1) Parental decision-making in sending their children to public primary schools in Luang Prabang Municipality, Luang Prabang Province, was found to be at a high level overall. Key factors included: reasonable registration fees and expenses suitable for family economic conditions; personnel and teachers having good human relations and being ready to provide advice; school buildings and environments being safe and conducive to learning; and confidence in the school's reputation and educational standards. 2) Parental opinions regarding the factors influencing their decision-making, both overall and in each individual dimension, were rated at a high level across five dimensions: personnel within the school, school buildings and environment, expenses, school reputation, and instructional management.3) The Multiple Regression Analysis (MRA) revealed that the factors influencing parents' decision-making in sending their children to public primary schools in Luang Prabang Municipality were: personnel within the school, school buildings and environment, and expenses. These three factors together could significantly predict parental decision-making at a rate of 73.8% with .